Mapping the impact of social media for innovation: the role of social media in explaining innovation performance in the PDMA Comparative Performance Assessment Study - Roberts, Deborah L.; Piller, Frank; Lüttgens, Dirk (Wiley, 2016)
Social media (SM) allow users to easily create, edit, or share content. The vast numbers of individuals that converge around sites like LinkedIn, Facebook, or Twitter embody a rich source of external knowledge that could be utilized for new product development (NPD). Complementing other channels for open innovation, SM can provide access to novel information about customer needs and technological solutions unknown to the firm. Anecdotal evidence suggests that there are considerable benefits from using SM during an innovation project, but empirical evidence is scare. Contributing to the perspective of openness in search, a number of hypotheses propose how SM as a new channel for open innovation can contribute to firm performance. This model is tested using data from the PDMA Comparative Performance Assessment Study (CPAS), identifying factors influencing the relationship between SM and NPD performance. The findings indicate that utilizing information from SM channels can lead to higher performance, but that this link is influenced by the formalization of a firm's NPD process. This study also finds that the ability of a firm to benefit from external search in SM strongly depends upon complementary internal processes when organizing and conducting this activity. Furthermore, managers have to take care when utilizing information from SM channels in radical projects, as for this kind of projects only a weak significant performance contribution of SM could be found.